Prednisolone treatment and restricted physical activity further compromise bone of mdx mice - Novotny, Susan A. (2012)
OBJECTIVES: The purpose of this study was to determine the extent to which prednisolone treatment and restricted physical activity caused deleterious changes in inherently compromised mdx bone. METHODS: Four week-old male mdx mice (n=36) were treated for 8-wk either with or without prednisolone (0.8–1.3 mg/kg/d) and were housed in traditional or small cages (restricted activity). Tibial bone strength, geometry, and intrinsic material properties were assessed at the mid-shaft by three-point bending and micro-computed tomography (μCT). RESULTS: Three-point bending results showed that both prednisolone and restricted activity reduced bone strength (7%), however stiffness was only reduced in restricted-activity mice. μCT analyses showed that cortical bone area and cortical thickness were 13% smaller in restricted-activity mice, and may have accounted for their compromised bone strength. Intrinsic material properties, including volumetric bone mineral density (vBMD) and modulus of elasticity, were not impacted by either treatment, however, vBMD tended to be lower in restricted-activity mice (p=0.06). CONCLUSIONS: These data show that prednisolone treatment and restricted physical activity independently accentuate reductions in the strength and geometry of mdx bone, but do not influence intrinsic material properties.